Implementasi Good Corporate Governance dan Etika Bisnis di PT Bank Mandiri (Persero) - Haryono, Haryono; Handayani, Henni Rahayu; Rosini, Nanik Ida (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
The necessity for high-quality implementation of Good Corporate Governance (GCG) arises from the increasing and complex risks and challenges faced by banks, both internally and externally. An intriguing area of research within GCG is the application of GCG principles and business ethics, ensuring that banks adhere to Bank Indonesia regulations with principles of transparency, accountability, responsibility, independence, and fairness, aligned with applicable laws and internal bank policies. The government's role, through the Ministry of State-Owned Enterprises (BUMN), Bank Indonesia, and the Financial Services Authority, is crucial in issuing regulations and policies to support GCG implementation in government-owned banks. The short-term objective of this research is to explore, describe, and analyze the implementation of GCG and business ethics to promote robust bank governance. This qualitative research aims to provide a comprehensive and systematic depiction of GCG implementation and business ethics. The analytical aspect of the study involves examining the data from a legal perspective, particularly concerning GCG implementation and business ethics. This research was conducted from November 2023 to March 2024, and its findings are expected to contribute to the development of business law and banking knowledge, specifically regarding the implementation of good corporate governance and business ethics.